2018
DOI: 10.1126/scitranslmed.aam8434
|View full text |Cite
|
Sign up to set email alerts
|

GABA A receptor availability is not altered in adults with autism spectrum disorder or in mouse models

Abstract: Preliminary studies have suggested that γ-aminobutyric acid type A (GABAA) receptors, and potentially the GABAAα5 subtype, are deficient in autism spectrum disorder (ASD). However, prior studies have been confounded by the effects of medications, and these studies did not compare findings across different species. We measured both total GABAAand GABAAα5 receptor availability in two positron emission tomography imaging studies. We used the tracer [11C]flumazenil in 15 adults with ASD and in 15 control individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 68 publications
(67 reference statements)
2
42
1
Order By: Relevance
“…Although both groups are matched for age, there is a trend level difference in age between antipsychoticfree patients and healthy controls (p = 0.06). Importantly, the V T values in our healthy control cohorts are similar to the ones reported in other studies using the [11C]Ro15-4513 PET tracer [51,43], indicating that our findings are not driven by abnormal values in our controls. Furthermore, α5-GABAARs show developmental reductions and, supporting this, in healthy volunteers there is an inverse relationship between age and [ 11 C]Ro15-4513 V T values.…”
Section: Strengths and Limitationssupporting
confidence: 89%
See 1 more Smart Citation
“…Although both groups are matched for age, there is a trend level difference in age between antipsychoticfree patients and healthy controls (p = 0.06). Importantly, the V T values in our healthy control cohorts are similar to the ones reported in other studies using the [11C]Ro15-4513 PET tracer [51,43], indicating that our findings are not driven by abnormal values in our controls. Furthermore, α5-GABAARs show developmental reductions and, supporting this, in healthy volunteers there is an inverse relationship between age and [ 11 C]Ro15-4513 V T values.…”
Section: Strengths and Limitationssupporting
confidence: 89%
“…GABA-A receptor availability was indexed using the distribution volume (V T ) of [ 11 C]Ro15-4513. In agreement with previous publications [43,44], the V T was calculated using with the metabolite-free arterial plasma input function and the twotissue compartmental model (2TCM) solved with a nonlinear least squares approach for the regional level and the Logan graphical method at the voxel level [45].…”
Section: Image Acquisitionmentioning
confidence: 80%
“…Reduced inhibition, leading to a net increase in the ratio of excitation/inhibition, is frequently hypothesized as a core pathophysiological mechanism in autism [6][7][8] . It has also been suggested that abnormal visual suppression observed in clinical populations may reflect dysregulation in the strength of underlying inhibitory mechanisms 16,20,44,[52][53][54] . However, we did not find evidence to suggest a difference in inhibition between participants with ASD and NTs; MR spectroscopy measurements of GABA+ in visual cortex did not differ between groups ( Figure 3C and Supplemental Figure 2C), and were not correlated with neural or perceptual measures of suppression ( Figure 3E-F).…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence for a widespread reduction in inhibition is either indirect or inconclusive. For example, there is evidence for decreased inhibition from genetic models of ASD in mice 7,[9][10][11] , but results in humans remain equivocal 8,[12][13][14][15][16][17] . An alternative is that modulatory processes that suppress neural responses, but do not rely directly on neural inhibition, are either disrupted or differentially engaged in ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs) across the GABRA5 and GABRB3 genes (respectively, coding for the α5 and β3 subunits of the GABA A α5 receptor) are associated with ASD [41,42]. A reduced density of GABA A α5 receptors was initially detected in the brain of ASD patients [43], a result that was not replicated in further studies [44]. Mice lacking the β3 subunit of the GABA A receptor (Gabrb3 -/mice) show ASD-relevant traits such as reduced sociability [45] and abnormal response to tactile stimulation [46], thus strengthening the importance of the GABA A α5 receptor subtype in ASD pathogenesis.…”
Section: Altered Expression Of Gaba Receptor Subunits In Young and Admentioning
confidence: 99%